Fruit drying traditions in Hungary - Surányi, D. (International Journal of Horticultural Science, 2017)
Since the early eras of human history, the gathered products (roots, shoots, crops, fruits etc.), the environmental conditions of the preservation of the animals caught and the fishes; and accidental observations have been born new methods. Under cold and moderate climates, the effect of permanent frost, the use of ice as a means of curing as in dry, desert areas is the drying or exsiccation and the dehydration of salt. For convenience reasons, some of these methods have been forgotten, but the resurfacing of different fruits seems to resume. The short review gives an overview of the methods of drying used in the Carpathian Basin, especially among the Hungarian ethnic groups, which by the Hungarian ethnology thoroughly explored. The author attaches outstanding importance to the fruit-drying industry, because dried-ups at industrial scale are not equivalent to traditional low-fat lime scales. Excellent drying products are much better in terms of eating habits, with modern methods and small-scale production relatively easy to produce.